Effects of exposure to an extremely low frequency electromagnetic field on hippocampal long-term potentiation in rat - Komaki, Alireza; Khalili, Afshin; Salehi, Iraj; Shahidi, Siamak; Sarihi, Abdolrahman (Brain research, 2014)
Modern lifestyle exposes nearly all humans to electromagnetic fields, particularly to extremely low frequency electromagnetic fields (ELF-EMFs). Prolonged exposure to ELF-EMFs induces persistent changes in neuronal activity. However, the modulation of synaptic efficiency by ELF-EMFs in vivo is still unclear. In the present study, we investigated whether ELF-EMFs can change induction of long-term potentiation (LTP) and paired-pulse ratio (PPR) in the rat hippocampal area. Twenty-nine adult male Wistar rats were divided into 3 groups (ELF-EMF exposed, sham and control groups). The ELF-EMF group was exposed to a magnetic field for 90 consecutive days (2h/day). ELF-EMFs were produced by a circular coil (50Hz, 100 micro Tesla). The sham-exposed controls were placed in an identical chamber with no electromagnetic field. After this period, rats were deeply anesthetized with urethane (2.0mg/kg) and then a bipolar stimulating and recording electrode was implanted into the perforant pathway (PP) and dentate gyrus (DG), respectively. LTP in hippocampal area was induced by high-frequency stimulation (HFS). Prolonged exposure to ELF-EMFs increased LTP induction. There was a significant difference in the slope of EPSP and amplitude of PS between the ELF-EMF group and other groups. In conclusion, our data suggest that exposure to ELF-EMFs produces a marked change in the synaptic plasticity generated in synapses of the PP-DG. No significant difference in PPR of ELF-EMF group before and after HFS suggests a postsynaptic expression site of LTP. •Exposure to electromagnetic fields is increasing with use of electrical appliances.•Extremely low frequency electromagnetic fields (ELF-EMFs) produces effects on cognition.•Exposure to ELF-EMFs induces persistent changes in long-term potentiation (LTP).•ELF-EMFs have no significant effects on paired-pulse ratio (PPR).•No significant difference in the PPR of ELF-EMFs, suggests a postsynaptic site of LTP.